Long Non-coding RNAs as Communicators and Mediators Between the Tumor Microenvironment and Cancer Cells - Chen, Di; Lu, Tong; Tan, Junying; Li, Hao; Wang, Qiuyue; Wei, Liangzhou (Frontiers in Oncology, 2019)
Long non-coding RNAs (lncRNAs) are a class of more than 200 nucleotides RNA transcripts which have limited protein coding capacity. They regulate numerous biological processes in cancers through diverse molecular mechanisms. Aberrant expression of lncRNAs has been frequently associated with human cancer. Furthermore, the tumor microenvironment (TME) is composed of different cells such as cancer-associated fibroblasts (CAFs), endothelial cells and infiltrated immune cells, and all of which participate in communication with tumor cells affecting the progression of tumor. LncRNAs are directly and indirectly involved in the crosstalk between stromal cells and tumor cells and dysregulated lncRNAs expression in these cells could drive tumorigenesis. In this review, we explore the influence of aberrantly expressed lncRNAs in tumor progression, clarify the critical roles of lncRNAs in the TME, summarize findings on crosstalk between infiltrated immune cells, CAFs, endothelial cells, and tumor cells via lncRNAs, and discuss the promise of lncRNAs as tumor diagnostic markers and therapeutic targets.